Mitigating physical climate risks: ESG budgeting approaches as risk boundaries for companies - Putri Wika Harisa; Bakhtiar Irfan; Mahasabha Ni Luh Ayounik (BIO Web of Conferences)
Physical climate risks are currently an urgent concern for companies. Many still consider this risk part of operational risk and manage it by transferring it to third parties. However, this method is still used to calculate the potential loss of assets due to physical climate risks. This paper explores ongoing literature and publications to address mitigating physical climate risk, and finds that companies increasingly turn to ESG budgeting approaches as a more comprehensive tool for managing direct and indirect physical climate risks. This study aims to synthesize the current literature and present a definition of ESG budgeting. This article will explore the various concerns regarding ESG budgeting and provide a technical overview of how companies manage and disclose these risks in their corporate statements. As a conceptual paper, no data was collected to provide empirical evidence to support ESG budgeting practices; instead, the concept of ESG-related cost or sustainable budget tagging was described. Technical steps are needed by companies, especially for those who still understand ESG in the initial phase. Apart from concerns about budget allocations that will increase, doubts that ESG spending will directly impact company financial performance are strong in implementing ESG in companies. This exploration found that the clear concept of ESG budgeting or ESG budget tagging is still rare and needs advanced discussion. A supportive ecosystem, a strong tone from the top and adequate ESG literacy are needed to ensure companies' readiness to mitigate physical climate risks.